2004
DOI: 10.1093/jb/mvh126
|View full text |Cite
|
Sign up to set email alerts
|

Abundant Retention and Release of Connective Tissue Growth Factor (CTGF/CCN2) by Platelets

Abstract: Wound healing and tissue regeneration are usually initiated by coagulation followed by fibrous tissue formation. In the present study, we discovered an abundance of connective tissue growth factor (CTGF/CCN2) in human platelets, which was released along with the coagulation process. The CTGF/CCN2 content in platelets was 10-fold higher than that in arterial tissue. Furthermore, the CTGF/CCN2 content in a single platelet was computed to be more than 20-fold higher than that of any other growth factor reported. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
64
0
7

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(71 citation statements)
references
References 0 publications
0
64
0
7
Order By: Relevance
“…This increase supports the theory that PRP increases neoangiogenesis 31 . Kubota et al 32 showed that growth factors of connective tissue also increased angiogenetic activity and fibrosis. Similar to the studies in the literature, our study found that after day 4, PRP increased granulation tissue and angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…This increase supports the theory that PRP increases neoangiogenesis 31 . Kubota et al 32 showed that growth factors of connective tissue also increased angiogenetic activity and fibrosis. Similar to the studies in the literature, our study found that after day 4, PRP increased granulation tissue and angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…We reported previously remarkably high levels of connective tissue growth factor (CTGF/CCN2) in human platelets released during the coagulation process (11). CTGF/CCN2 is a cysteine-rich secretory protein of 36 to 38 kDa, which is composed of 349 amino acid residues, and its gene belongs to the CCN family, which consists of cef10/cyr61, ctgf/fisp12, nov, and several recently reported genes, such as elm1/wisp1, ctgf3/ctgfL/wisp2/cop1, and wisp3 (12 -17).…”
Section: Introductionmentioning
confidence: 99%
“…Also of importance are transforming growth factor-beta (TGF-b) (Rosier et al1998), vascular endothelial growth factor (VEGF) (Rhee et al 2004), smaller amounts of insulin-like growth factor (IGF) (Weibrich et al 2002a) and epidermal growth factor (EGF) (Martin et al 1992). Additionally, Kubota and others described that connective tissue growth factor (CTGF) is also present (Kubota et al 2004). Recently, strategies in clinical treatment plans encourage the production of autologous platelet-rich plasma (PRP) containing high concentrations of platelet growth factors with the use of whole blood separation devices.…”
mentioning
confidence: 99%